2018
DOI: 10.1523/jneurosci.0612-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Somatosensory Processing and Connectivity in Mice LackingEngrailed-2

Abstract: Overreactivity and defensive behaviors in response to tactile stimuli are common symptoms in autism spectrum disorder (ASD) patients. Similarly, somatosensory hypersensitivity has also been described in mice lacking ASD-associated genes such as Fmr1 (fragile X mental retardation protein 1). Fmr1 knock-out mice also show reduced functional connectivity between sensory cortical areas, which may represent an endogenous biomarker for their hypersensitivity. Here, we measured whole-brain functional connectivity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 75 publications
5
79
0
Order By: Relevance
“…Males were indeed characterized by a higher neuronal cell area and a lower cell density. These gender-related morphological differences have never been reported in studies performed in this mice strain; nor, likewise, have any gender-related differences of behavioral traits and gene expression profiles (Brielmaier et al 2012;Sgadò et al 2013;Chelini et al 2018). However, evidence of gender differences in the brain structure was found in young children with ASD (Retico et al…”
Section: Effect Of Gendermentioning
confidence: 79%
“…Males were indeed characterized by a higher neuronal cell area and a lower cell density. These gender-related morphological differences have never been reported in studies performed in this mice strain; nor, likewise, have any gender-related differences of behavioral traits and gene expression profiles (Brielmaier et al 2012;Sgadò et al 2013;Chelini et al 2018). However, evidence of gender differences in the brain structure was found in young children with ASD (Retico et al…”
Section: Effect Of Gendermentioning
confidence: 79%
“…However, atypical sensory reactivity represents early markers of autism and are predictive of social-communication deficits and repetitive behaviors in childhood. Although recent findings performed in mouse ASD genetic models report sensory deficits(Chelini et al, 2019; Cheng et al, 2017; Drapeau et al, 2018; Huang et al, 2019; Orefice et al, 2016; Siemann et al, 2017), they were explored during juvenile or adult period. Whether sensory dysfunctions might be present at the early life stage is something unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Much of research in animal models of syndromic and non-syndromic forms of ASDs has focused on the social and cognitive difficulties and their underlying mechanisms (Robertson and Baron-Cohen, 2017). Recent increasing evidences suggest that sensory traits such as tactile, visual, auditory, olfactory, gustatory and heat abnormalities (Chelini et al, 2019; Cheng et al, 2017; Drapeau et al, 2018; Huang et al, 2019; Orefice et al, 2016; Siemann et al, 2017) are present in ASD models, yet the existence of sensory dysfunctions during early life period have been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Mice were assigned a numerical code by an operator who did not take part in the experiments, and codes were associated to genotypes only at the moment of data analysis. Experiments were performed on mice of both sexes, since previous studies did not reveal major significant differences between sexes at molecular, anatomical, and behavioral level [17,19,22].…”
Section: Animalsmentioning
confidence: 99%
“…Genome-wide association studies identified En2 as a candidate gene for ASD [13]; accordingly, mice lacking En2 [14] display cerebellar defects resembling those reported in ASD subjects [15]. In addition, En2 -/mice present a series of pathological behaviors that are reminiscent of some features of ASD individuals, including reduced social interactions, defective spatial learning, and sensory processing deficits [16][17][18][19]. As frequently observed in ASD patients, En2 -/mice display an increased susceptibility to seizures [10,20] accompanied by the altered expression of ASD-and seizure-relevant genes [21].…”
Section: Introductionmentioning
confidence: 97%